The Impact of Political Literacy Education and Learning on the Political Participation of First-Time Voters Ahead of the 2024 Election in Kerinci Regency - Revalina, Atiqah; Suryanef, Suryanef; Rafni, Al; Putra, Eka Vidya; Ockta, Yovhandra (JETL (Journal of Education, Teaching and Learning), 2024)
In a democratic country, political literacy is a very important aspect in elections because the higher the political literacy of its citizens, the higher the quality of democracy implementation in the country. Political literacy will create a politically literate society, if there is a lack of political literacy, it will have an impact on the quality of participation. This study aims to find out the level of political literacy of novice voters, find out the level of political participation of novice voters and find out the quality of the correlation between the political literacy of novice voters and their political participation ahead of the 2024 general election. This research is located in Air Hangat Barat District, Kerinci Regency. This study uses a descriptive-correlational method. The data collection technique used is a questionnaire. The sampling technique used is probability sampling, which is simple random sampling. Data analysis was carried out by Pearson correlation test analysis, which was first carried out as a prerequisite for analysis, there was a significant positive relationship between the political literacy of novice voters and political participation ahead of the 2024 election, showing a significance value of p < 0.05. The value of the product moment correlation between x and y is only at 0.409 from the interval of 0.40-0.599, so it is concluded that it is "quite strong" even though it is not at a very high level, because not only political literacy affects novice voters to participate but many other factors can influence novice voters to participate in activities ahead of the general election.